The Edwardian Selfies: A transhistorical approach to celebrity culture and pictorial bookplates. (October 2021) - O'Hagan, Lauren Alex; Spilioti, Tereza
Highlights: Transhistorical approach places selfies within history of technological change. Bookplate and selfie users draw on semiotics to conduct performances of self. Concerns of authenticity and superficiality govern bookplates and selfies. In both media, high importance is given to societal norms and subscribed behaviours. Some bookplates, nonetheless, challenge the status quo. Selfies and bookplates are guided by different norms, despite their similar forms. Abstract: In this paper, we will explore, through a narrative-semiotic lens, how 32 Edwardian (1901–1914) celebrities style the 'self' in their pictorial bookplates. Using Zhao and Zappavigna (2018a; 2018b; 2020) and Ross and Zappavigna's (2019) typology of selfies as a starting point and drawing upon aspects of Bamberg and Georgakopoulou's (2008) positioning analysis, we will embed users' visual arrangements and narrative stance-taking elements in ethnohistorical insights gathered from archival research. Grounding these choices in evidence from their original sociohistorical context of creation will demonstrate that, like selfies, pictorial bookplates are dynamic multimodal ensembles that enable users to construct multiple identities and achieve different communicative goals. However, it will offer a more nuanced perspective into the relationship between 'new' and 'old' media, suggesting that, despite the similar forms and functions of pictorial bookplates and selfies, their creation is guided by different ideological values and bounded by the affordances, norms and traditions of the time. The methodology and findings presented in this paper will contribute to the growing body of transhistorical research that is concerned with situating communication technologies in the wider history of technologically mediated change.